Kualitas fisik susu goreng dengan waktu penyimpanan dingin yang berbeda - Haris Wahyudi; Metha Monica; Fatati Fatati (Jurnal Ilmu Peternakan Indonesia, 2026)
This study aimed to analyze the effect of cold storage duration on the physical quality of fried milk, including pH, moisture content, and yield. A Completely Randomized Design (CRD) was used with four storage treatments (0, 1, 2, and 3 hours) at 4°C and five replications. The results showed that increasing storage time significantly decreased pH and moisture content. The pH value declined from 7.29 at 0 hours to 7.23 at 3 hours, indicating increased acidity. Moisture content decreased from 29.8% to 24% due to water evaporation during cold storage. The highest yield was obtained at 2 hours of storage (11.02%) and slightly decreased at 3 hours. It can be concluded that storage for 2 hours at 4°C was the optimal treatment for maintaining the physical quality of fried milk while ensuring product safety and shelf life.